N-Type Superconductivity in an Organic Mott Insulator Induced by Light-Driven Electron-Doping - Masayuki Suda (2018)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim The presence of interface dipoles in self-assembled monolayers (SAMs) gives rise to electric-field effects at the device interfaces. SAMs of spiropyran derivatives can be used as photoactive interface dipole layer in field-effect transistors because the photochromism of spiropyrans involves a large dipole moment switching. Recently, light-induced p-type superconductivity in an organic Mott insulator, κ-(BEDT-TTF)2Cu[N(CN)2]Br (κ-Br: BEDT-TTF = bis(ethylenedithio)tetrathiafulvalene) has been realized, thanks to the hole carriers induced by significant interface dipole variation in the spiropyran-SAM. This report explores the converse situation by designing a new type of spiropyran monolayer in which light-induced electron-doping into κ-Br and accompanying n-type superconducting transition have been observed. These results open new possibilities for novel electronics utilizing a photoactive SAMs, which can design not only the magnitude but also the direction of photoinduced electric-fields at the device interfaces.